The roles of personal resources and transformational leadership on work engagement and its impact on job performance among the academic staff - Wong, Cherry Xin Ying; Kong, Irene Ji Cheng; Lai, Chun Weng; Lai, Siew Kei; Ong, Xin Yi (2020)
Education industry is important to all of us especially the higher education as the act as the key role in the knowledge economy and able to contribute national human capital with the highest standard of skill and knowledge. Each of the parties have responsibility to increase the employee engagement which able to increase the job performance for each of academic staff in the private university. Recently, there found that the employee engagement has become decreasing in the education industry especially in private university. Hence, the research’s purpose is to investigate the factors which are personal resources (Self-efficacy, optimism, resilience and hope) and transformational leadership that affect work engagement toward job performance among academic staff in Malaysia private education industry. In this research, researchers conduct the survey to collect the primary source by distributing 300 set of questionnaires to the target population where located at Universiti Tunku Abdul Rahman (UTAR), Kampar Campus. Researchers conducted the Cronbach’s alpha reliability test on every construct which resulted high reliability test. Moreover, Pearson correlation coefficient, multiple regression, and linear regression revealed the importance of independent variables. In the results shown that the independent variables which included personal resource (Self-efficacy, optimism and, hope) and transformational leadership have a positive relationship whereas resilience has a negative relationship with work engagement (dependent variable) while the work engagement has a positive relationship with the job performance (dependent variable) .Education sector should implement proper strategy which would increase the employee engagement toward to have better job performance for each of the academic staff. Overview of the research tends to provide investigate the factors which affecting the work engagement in Malaysia Education industry. Throughout this research, the limitations of the study have been identified. Hence, it should be avoided the similar limitation in the future research. Besides limitation, the discussion of findings, implications of the study and recommendations for future research will be conducted in the end of this study.